1993
DOI: 10.1021/ma00063a046
|View full text |Cite
|
Sign up to set email alerts
|

Single-chain polystyrene glasses

Abstract: The microemulsion free-radical polymerization of styrene generates particles containing one or at most a few high molecular weight polymer chains. Space-filling considerations preclude such chains from adopting their random-coil conformation; rather, they adopt a highly compact globular conformation and below Te constitute essentially single-chain glasses. This paper reports apparent spectroscopic and thermal differences between single-chain and conventional multichain polystyrene glasses. FTIR measurements su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 3 publications
4
45
0
Order By: Relevance
“…On the other hand, the data from material freeze-dried from 0.02% polymer solutions are 2-3 K above model predictions, indicating that in the absence of residual solvent effects, we may have an increase in T g of this magnitude for polystyrene freeze-dried from the 0.02% solutions. In support of such a conclusion is the observation of an elevated T g for single-chain polystyrene glasses obtained via a microemulsion process [38] and the fact that entropic considerations would predict such an elevation of T g for freeze-dried polymers [12] and for polymers confined to thin films [39].…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the data from material freeze-dried from 0.02% polymer solutions are 2-3 K above model predictions, indicating that in the absence of residual solvent effects, we may have an increase in T g of this magnitude for polystyrene freeze-dried from the 0.02% solutions. In support of such a conclusion is the observation of an elevated T g for single-chain polystyrene glasses obtained via a microemulsion process [38] and the fact that entropic considerations would predict such an elevation of T g for freeze-dried polymers [12] and for polymers confined to thin films [39].…”
Section: Discussionmentioning
confidence: 93%
“…[1] Bu et al [2][3][4] observed the formation of single crystals of single chains of poly(oxyethylene) and isotactic polystyrene by means of transmission electron microscopy (TEM). Later on, Qian et al [5] reported some basic properties of the single-chainstate of atactic polystyrene. Cheng et al [6] claimed that, in order to prepare polymers in the single-chain-state from solution, the concentration must be below the dynamic contact concentration (C s ) [7,8] in addition to the static contact concentration (overlap concentration C*).…”
Section: Introductionmentioning
confidence: 99%
“…This structure is believed to be the result of local molecular packing arrangements upon annealing, which later was termed as cohesional entanglements (CE for short), a kind of binary or multiple inter-chain cohesion (attractive interaction) with local parallel alignment of neighboring chain segments. [10,11] A similar idea that is in complete accord with the concept of CE was first raised by Raha and Bowden, by the name of 'cohesional points', to explain the strain behavior of rubber at yielding. [12] In order to achieve evidence for the unlocking of CE as a mechanism of yielding for glassy polymers, DSC was used to monitor in detail the process of stretch of aged a-PS.…”
Section: Resultsmentioning
confidence: 79%